SM 05-0921 Distracted walking among teens in the U.S.: analysis of observations. (November 2018) - Rosenthal, Kristin; MacKay, Morag
Abstract : Pedestrian fatalities in 13–19 year olds have increased by 19% in the last two years. To determine any changes in the level of distracted walking among teenagers in the U.S., research examined the percentage of teenagers crossing the street near schools while distracted in a sample of communities in 2016 and compared them to findings from a previous observational survey in 2013. Baseline observations were made of more than 18 000 of teens crossing streets near middle- and high-schools in 20 communities. Observers conducted two morning and afternoon sessions, at the same times but on different school days, in good weather. Each observer focused on one crossing location. Following the initial set of observations, we stenciled 'Heads Up Phones Down' in paint on curb ramps in the school zone and a minimum of two-weeks later repeated the observations to assess the impact on distracted behavior. Levels of distraction were 17% for middle-school students and 27% for high-school students. This was a statistically significant increase from distraction levels observed in 2013. The odds of a girl crossing while distracted were greater than of a boy. In addition to distraction, 80% of students displayed at least one other unsafe crossing behavior. Assessment of the intervention was based on 35 009 observations at schools participating in both observation periods. We found a significant decrease in distracted walking. The odds of crossing the street distracted were 30% lower after the intervention. Interestingly, when pedestrian distraction decreased, other unsafe pedestrian behaviors, such as crossing mid-block, also increased. Distracted walking has been identified as a potential factor for recent increases in child pedestrian fatalities in the U.S. Our simple, inexpensive, real-time intervention was effective in reducing distraction, although the length of follow-up was short.